TANGGUNG JAWAB PELAKU USAHA TERHADAP KONSUMEN YANG MENGALAMI KERUGIAN AKIBAT TIDAK DICANTUMKANNYA INFORMASI MENGENAI KOMPOSISI PRODUK SECARA LENGKAP - Adi Merta Jaya, Putu; Mas Aryani, Ni Nyoman (Kertha Semaya : Journal Ilmu Hukum, 2013)
This writing shall be entitled as “Producer’s Liability due to Incomplete Information of Product Composition towards Consumer”. This writing is composed by normative legal research method combined with statutory approach. Thus, this writing shall reiterate the importance of completed information facts of certain product and producer liability towards the damage possibly experienced due to the incomplete information given.
Keywords: Consumer, Producer, Responsibility, Product